2010
DOI: 10.1515/hmbci.2010.063
|View full text |Cite
|
Sign up to set email alerts
|

Cancer protection of soy resembles cancer protection during pregnancy

Abstract: It has been established that carrying a pregnancy to full-term at an early age can protect against contracting cancer by up to 50% in later life. The trophoblast theory of cancer states that trophoblast and cancer tissue are very similar. New findings suggest that the loss of fetal cells during pregnancy resemble those cells responsible for causing metastasis in cancer. Fetal cells and spreading cancer cells are highly proliferative. They are similar to stem cells, exhibiting no or low hormone receptor express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 154 publications
0
15
0
Order By: Relevance
“…was diagnosed as cancer-free 11-h surgery: colon conduit is performed (and elimination of nephrostomy). After surgery, no wound healing problems were detected Tissue samples show no cancer cells Patient was still under FSWW08 nutrition Th1-cytokine formation [16] . Therefore, the improvement of blood hematology and cachexia may very well be related to improvement in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…was diagnosed as cancer-free 11-h surgery: colon conduit is performed (and elimination of nephrostomy). After surgery, no wound healing problems were detected Tissue samples show no cancer cells Patient was still under FSWW08 nutrition Th1-cytokine formation [16] . Therefore, the improvement of blood hematology and cachexia may very well be related to improvement in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In light of interesting findings from animal studies [10] and human studies [9,15,16] , a study was initiated to investigate whether a soy product, FSWW08, would increase hematopoiesis and increase appetite in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, soy baby nutrition formulation has no effect on the immune system of babies, which have similar isofl avone doses as FSWW08, when compared with a person with a body weight of 80 kg (about 500 -900 mg isofl avones) [69,70] . It was suggested that the immune system of a newborn is not fully developed [20] . Production of DHEA by the adrenal reticularis is a species-specifi c phenomenon; rodents have little circulating DHEA and the pattern of DHEA secretion differs between human and non-human primates [71] .…”
Section: Hormonementioning
confidence: 99%